2021
DOI: 10.1371/journal.pone.0244911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transport and altitude on hormones and oxidative stress parameters in sheep

Abstract: In study, it was aimed to determine the stress effects that can be caused by transporting and altitude in sheep. Karayaka sheeps were used in the study. Karayaka sheeps are a valuable breed of meat quality and fleece, which is raised in the Black Sea region. The live weight of the sheep (n = 30) while hungry was determined before transport and sea level. Average live weight was determined as 55.64 ± 4.66 kg. Blood samples were collected just before (sea level) and just after transport (1500 meters above sea le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A large amount of hydrogen peroxide can damage tissue cells, and CAT catalyzes hydrogen peroxide into water and oxygen, which reduces the damage to the organism. T-AOC indicates the total antioxidant capacity of the organism [32], and the MDA content directly determines the degree of lipid peroxidation of the organism, it is an important indicator for the organism to evaluate the damage of lipid oxidation, and also indirectly reflects the degree of damage of the intestinal mucosal cells [33]. In the present experiment, we examined the content of each antioxidant index in the liver of Ira rabbits and found that MOAs increased CAT content and decreased MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of hydrogen peroxide can damage tissue cells, and CAT catalyzes hydrogen peroxide into water and oxygen, which reduces the damage to the organism. T-AOC indicates the total antioxidant capacity of the organism [32], and the MDA content directly determines the degree of lipid peroxidation of the organism, it is an important indicator for the organism to evaluate the damage of lipid oxidation, and also indirectly reflects the degree of damage of the intestinal mucosal cells [33]. In the present experiment, we examined the content of each antioxidant index in the liver of Ira rabbits and found that MOAs increased CAT content and decreased MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is expressed as a typical stress reaction that animals are exposed to during transport. In addition, poor road conditions, driving performance of drivers, transport conditions, road length, climate, lack of water and feed can cause stress in animals during transport [19,129,130]. Some studies have shown that the main factors affecting the welfare of sheep during road transport are driving behavior, noise, acceleration, road type [131,132], vehicle design [133,134], transport intensity [135], duration of the journey [136,137] and transport of different breeds together, new environment, hunger, thirst and fatigue [133], excessive ventilation, cold or heat stress [138,139].…”
Section: Transportation and Treatment Stressmentioning
confidence: 99%
“…The results showed that increased transport time significantly increased body weight loss and decreased hematocrit, cortisol, and glucose values in blood. Tozlu Çelik et al ( 2021) [19] aimed to determine the effects of transport and altitude in Karayaka sheep. The results obtained showed that transport and altitude significantly affected triiodothyronine, tyrosine, and oxidative stress parameters of malondialdehyde (MDA), so these factors were reported to cause stress in sheep.…”
Section: Transportation and Treatment Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Çelik et al [33] reported that OS in sheep, caused by a change in altitude, could be reduced by supplementing the feed with antioxidants. This appears to prevent OS from negatively affecting meat quality in sheep.…”
Section: Introductionmentioning
confidence: 99%